2019
DOI: 10.1038/s41467-019-12041-8
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous whole-genome duplication restores fertility in interspecific hybrids

Abstract: Interspecies hybrids often show some advantages over parents but also frequently suffer from reduced fertility, which can sometimes be overcome through sexual reproduction that sorts out genetic incompatibilities. Sex is however inefficient due to the low viability or fertility of hybrid offspring and thus limits their evolutionary potential. Mitotic cell division could be an alternative to fertility recovery in species such as fungi that can also propagate asexually. Here, to test this, we evolve in parallel … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
61
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 65 publications
(79 reference statements)
6
61
0
Order By: Relevance
“…Similar results from Gallone et al 2016 andGonçalves et al 2016 showed that multiple populations of beer strains had high rates of tetraploidy. Although spontaneous yeast tetraploids are usually fertile (Charron et al 2019), the Jean-Talon strain shows about 30% spore viability ( Figure 1C), which is close to the average spore viability observed for beers from the genetic groups Beer2, Mixed and Mosaic in (Gallone et al 2016). The Jean-Talon is therefore typical of beer strains with respect to ploidy and fertility.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Similar results from Gallone et al 2016 andGonçalves et al 2016 showed that multiple populations of beer strains had high rates of tetraploidy. Although spontaneous yeast tetraploids are usually fertile (Charron et al 2019), the Jean-Talon strain shows about 30% spore viability ( Figure 1C), which is close to the average spore viability observed for beers from the genetic groups Beer2, Mixed and Mosaic in (Gallone et al 2016). The Jean-Talon is therefore typical of beer strains with respect to ploidy and fertility.…”
Section: Resultssupporting
confidence: 75%
“…Measurement of DNA content was performed using flow cytometry and the SYTOX green staining assay (Thermo Fisher, Waltham, USA) as done in (Charron et al 2019). Cells were first thawed from glycerol stock and streaked on solid YPD in six petri dishes (room temperature, three days) to obtain isolated colonies.…”
Section: Dna Content and Ploidymentioning
confidence: 99%
“…Moreover, natural hybrids are somewhat limited in their ability to uncover the interplay between hybridization and transposition, as they are relatively recent introgressed lineages that resulted from admixture between closely related lineages. To systematically explore the effect of hybridization on Ty transposition rates, we performed a large-scale mutation accumulation (MA) experiment on 11 artificial hybrid backgrounds, eight of which were previously published (Charron et al, 2019). A MA experiment with yeast consists of subjecting a population to periodic single-cell bottlenecks (typically during hundreds to thousands of mitotic generations) by streaking a randomly chosen single colony, thus amplifying genetic drift and making natural selection inefficient (Lynch et al, 2008) (Figure 6a).…”
Section: Te Content Variation In Experimental Evolution Under Relaxedmentioning
confidence: 99%
“…Crosses BB, BC, BA and BSc were previously published (Charron et al, 2019). CC crosses were performed following the same methodology.…”
Section: Mutation Accumulationmentioning
confidence: 99%
See 1 more Smart Citation